HOW TO TRANSFER COMPETENCIES INTO THE LEARNING CONTENT - Nikolay V. Sosnin (Высшее образование в России, 2016)
The article discusses the problem of content structure of competence2oriented learning. It is argued that the key issue in this problem is the way to transfer competencies of a graduate into learning content of educational program. Integrative and beyond2disciplinary nature of the competencies requires changes to traditional disciplinary model. A concept is proposed, according to which firstly the structure of the learning outcomes is designed and then it turns into the content of the structural units of the learning process.